Modern forests : statemaking and environmental change in colonial eastern India - Sivaramakrishnan, K. (New Delhi : Oxford University Press, 1999)
Modern Forests is an environmental, institutional, and cultural history of forestry in colonial eastern India. By carefully examining the impact of regional political formations and biogeographic processes on land and forest management, this book probes the interrelated social and biophysical factors that influenced landscape change.
Through a cultural analysis of powerful landscape representations, Modern Forests reveals the contention, debates, and uncertainty that persisted for two hundred years of colonial rule as forests were identified, classified, and brought under different regimes of control and were transformed to serve a broad array of imperial and local interests."--BOOK JACKET.
1. Statemaking and Environmental Change
Pt. 1. Intimations of a Governmental Rationality at the Margins of Empire. 2. British Entry into the Jungle Mahals. 3. Geographies of Empire: The Transition from 'Wild' to Managed Landscapes. 4. Visibility, Estimation, and Laying Down the Ground Rules
Pt. 2. Formal Structures of Forest Management. 5. Varied Regimes of Restriction and Lumbering. 6. Forests in a Regional Agrarian Economy. 7. Nature's Science: Fire and Forest Regeneration. 8. Science and Conservation: Hybrid Genealogies of Development. 9. Conclusion.
"This book has been prepared from the first volume of a two-volume historical and ethnographic study on statemaking and forest management in Bengal, completed as a PhD dissertation for the Department of Anthropology, Yale University"
includes bibliographical references (pages[290]-323) and index.
ARC
Department of Architecture
Keywords: Forest management -- India -- Bengal; Forest policy -- India -- Bengal